Development of Powtoon-Assisted Audiovisual Media in Mathematics to Improve Understanding of Elementary School Students - Prayuningtyas Angger Wardhani; Salsa Sabrina; Fahrurrozi Fahrurrozi (Wahana, 2023)
Mathematics is a subject that is considered not easy for student. The use of conventional learning methods such as lectures and the infrequent use of instructional media are considered to be the cause of the lack of interest and motivation of student to learn mathematics. The aims of this study is to develop an audiovisual learning media for mathematics on two-dimentional figure for class II elementary schools. The method used in this study is the Reseach and Development (R&D) method. The development model used is the ADDIE which consists of five stages, those are Analyze, Design, Development, Implementation, and Evaluation. The research subjects in this study were students from class II of SD Negeri Smanan 04 Pagi. The validation test results of mathematical audiovisual media on two-dimentional figure were declared very valid with the validity percentage value is 90-94 percents.